The application of the doctrine of a loss of a chance to recover in medical law - Pat van den Heever (Pretoria University Law Press (PULP), 2007)
About the publication In this book, Pat van den Heever assesses the application of the doctrine of a loss of a chance in medical negligence cases in South Africa. He emphasises the difficulties often encountered by courts when adjudicating on causation in medical negligence cases in the face of multiple causation theories. On the basis of a thorough review of the position regarding the doctrine of a loss of a chance in The United States of America, Australia and Britain, he proposes for South Africa a de lege ferenda loss of chance model for application in medical negligence matters. As the first ever major work dealing with the application of the doctrine of a loss of a chance in medical negligence matters in South Africa, this book is of interest to the courts and the legal profession generally, legal academics working in the field of medical law and the law of delict, health care providers, and members of the medical and allied professions, their councils, associations and protection societies. "This publication is the first authoritative and substantive research on the doctrine of a loss of a chance in the context of medical negligence in South African medical law ... Dr van den Heever's thorough and comprehensive comparative approach and discussion of the doctrine here, is commendable ... [T]his publication is indeed timely!" - Pieter Carstens, Professor of Medical Law, University of Pretoria